The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s10479-022-04961-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Periapical dental X-ray image classification using deep neural networks

Abstract: This paper studies the problem of detection of dental diseases. Dental problems affect the vast majority of the world's population. Caries, RCT (Root Canal Treatment), Abscess, Bone Loss, and missing teeth are some of the most common dental conditions that affect people of all ages all over the world. Delayed or incorrect diagnosis may result in mistreatment, affecting not only an individual's oral health but also his or her overall health, thereby making it an important research area in medicine and engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Table 5 clearly shows that most studies have shown the benefits of using pre-trained CNN models. Research on the teeth disease identification has been mostly restricted to limited comparisons of simulating the transfer learning methodology on some sort of CNN types, such as AlexNet [37] and VGG16 [36]. Some studies present an effort for the use of custom CNN models, such as CustomAlexNet [17], a fully convolutional network (FCN) [23] and a hybrid neural network (HNN) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 clearly shows that most studies have shown the benefits of using pre-trained CNN models. Research on the teeth disease identification has been mostly restricted to limited comparisons of simulating the transfer learning methodology on some sort of CNN types, such as AlexNet [37] and VGG16 [36]. Some studies present an effort for the use of custom CNN models, such as CustomAlexNet [17], a fully convolutional network (FCN) [23] and a hybrid neural network (HNN) [8].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, researchers have focused on validating the efficiency and accuracy of deep learning algorithms for analyzing intraoral X-ray images. After the development of CNNs, deep learning architectures for dental imaging evolved as the variations in CNNs, such as VGGNet [36], GoogLeNet [21], AlexNet [37], EfficientNet [38] and DenseNet [39]. For example, Lee et Convolutional neural networks (CNNs) are a type of artificial neural network that has been specifically developed to handle signals, sequences, images or volumetric data.…”
Section: One Of the Studies Is The Development Of A New Dentalmentioning
confidence: 99%
“…For accurate age estimates based on developmental changes, recurrent neural networks (RNNs) are particularly useful for identifying temporal dependencies in dental imaging sequences. Additionally, generative adversarial networks (GANs) have demonstrated potential in synthesizing high-quality dental pictures, assisting in data augmentation, and resolving issues related to small datasets [5]. Transfer learning methods have also improved efficiency during dental imaging tasks.…”
Section: Deep Learning Applications In Dental Radiographymentioning
confidence: 99%
“…The data used for the analysis were descriptive complaint questionnaires filled out by dental clinic patients in Japan. Although oral diseases are largely preventable, they affect the majority of the world's population, approximately 3.5 billion (Vasdev et al, 2022;World Health Organization, 2022). This means that oral health is an indispensable issue for customers.…”
Section: Introductionmentioning
confidence: 99%